Pemberdayaan Ibu Rumah Tangga melalui Tanaman Kangkung Guna Menciptakan Usaha Rumahan untuk Meningkatkan Ekonomi Keluarga di Desa Tugu Kecamatan Mantup - Juliyani, Erly; Siswadi, Siswadi; Azhar, Muhamad Malik; Nurhasanah, Nurhasanah; Putri Perdani, Novi; Rohmah, Salsabilatur (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2023)
The conditions in the field show that so far the utilization and management of rural resources is mostly done by men, starting from activities in agriculture, animal husbandry, small and medium industries, cooperatives, and other activities that are economic in nature. In fact, in society, women also have the right to use or manage existing resources in the village, although not completely like men. Therefore, it is necessary to have various activities that can be implemented for women in order to improve the family economy by utilizing and managing the surrounding environment. One of the programs that can be implemented by women in an effort to improve the family's economy, especially in the food sector is the Vegetable Plant Utilization (KANGKUNG) program. The purpose of this service is to improve the family's economy through an empowerment program for housewives in processing kale that is practical and minimalist in its manufacture. the method used is the ABCD method. So that the community can take advantage of existing assets in the surrounding environment to improve the family economy. In practice, how to process kangkung plants so that they become snacks and healthy. In its implementation there are several stages, namely analyzing problems, preparing program planning, program implementation and program evaluation. So the result of the mentoring program is that it has a significant impact on the community.